(untitled) (Journal of Eye Movement Research, 2012)
Several studies have shown that eye movements (EM) are functionally involved in visual imagery. In this study we investigate the impact of a simulated homonymous hemianopia paradigm (SH) with and without foveal masking on scanpath eye movements during visual mental imagery. EM of twenty subjects were recorded under SH condition during viewing and subsequent visual imagery of complex pictures. Using evaluated string editing methods viewing and imagery scanpaths were compared. Our results show that scanpath EM are involved in visual mental imagery and reflect the picture content even under SH. In contrast, additional foveal masking significantly reduces the similarity between viewing and imagery scanpath. This points toward a detrimental effect of foveal masking on subsequent visual imagery performance.